The Art and life of Alàgbà Fálétí – A Pic torial, Art and Artifacts Exhibition in Honor of Alàgbà Adébáyọ̀ Fálétí (1921- 2017) curated by Akinsola Adejuwon and Seyi Ogunjobi - Akinsola Adejuwon (Yoruba Studies Review)
Alàgbà Adébáyọ Fálétí to generations both in “town and gown” is a Yorùbá ̀ iconic cultural statement. His life was a window to different historical epochs in Nigeria. A life that spanned and recorded historical trajectories of early colonial, decolonisation, independent movement, First and Second World Wars, and Nigerian Civil War, Military and Civilian Rules experiences of Nigeria, is worth studying. The Institute of Cultural Studies, Obafemi Awolowo University Ile Ife in recognition of the deep engraving of the footprints of Fálétí in the sands of Yorùbá, indeed African times, called for befitting academic and cultural activities. Among these are this art and artifacts exhibition, a Colloquium, a Playlet and Documentary Film Show. Fálétí’s intense dedication to the promotion of the Yorùbá ọmọlúàbí cultural ethos and his deployment of his God-given talents and acquired capabilities in the promotion of Yorùbá literary and visual arts, history, poetry, orature, cinema and indeed 1 This is a review of the 2-week pictorial, art and artifacts exhibition in Honor of Alagba Adebayo Faleti in 2017 at the Institute of Cultural Studies, Obafemi Awolowo University, Ile-Ife, Nigeria, curated by Akinsola Adejuwon and Seyi Ogunjobi.